Mechanism of scavenger receptor-A in high glucose-induced inflammatory injury of mesangial cells - Xiao, H (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To investigate the effect of high glucose on scavenger receptor-A (SR-A) in human glomerular mesangial cells (HMC) and explore the mechanism of inflammatory injury mediated by SR-A in HMC cultured in high-glucose medium. Methods: According to the concentration of D-glucose in culture medium, HMC were divided into normal glucose group (5.5 mmol/L) and high glucose group (30 mmol/L), with mannitol group as hypertonic control. High glucose group was transfected with SR-A small interfering RNA (siSR-A) and the transfection control (siNC) group were set up. Western blotting technology was used to detect the levels of SR-A, NOD-like receptor family pyrin domain-containing 3 (NLRP3), interleukin-1β (IL-1β) protein. Immunofluorescent staining was applied to measure the SR-A in HMC. The mRNA of NLRP3, Caspase-1, IL-1β, FN, ColⅣ, α-SMA and GRP78 were detected by real-time quantitative PCR. The relative activity of Caspase-1 was detected by enzyme method and the concentration of IL-1β in culture medium was detected by enzyme linked immunosorbent assay. Flow cytometry was used to measure the cell cycles of HMC. One-way ANOVA and SNK-q test were used for statistical analysis. Results: The protein level of SR-A in high glucose group was higher than that in normal glucose group and mannitol group (1.23±0.21 vs. 0.68±0.10, 1.23±0.21 vs. 0.78±0.13, all P<0.05). In addition, mean fluorescence intensity of SR-A, protein levels of NLRP3 and IL-1β, mRNA of NLRP3, Caspase-1 and IL-1β, relative activity of Caspase-1 as well as the concentration of IL-1β in high glucose group were all significantly higher than those in normal glucose group and mannitol group (all P<0.05).After transfection induced silencing, SR-A protein in high glucose siNC group was higher than that in high glucose siSR-A group and normal glucose siNC group (1.23±0.10 vs. 0.20±0.01, 1.23±0.10 vs. 0.87±0.01, all P<0.01). In high glucose siNC group, the NLRP3, IL-1β proteins, the NLRP3, Caspase-1 and IL-1β mRNA, all of the mRNA levels of FN, ColⅣ, α-SMA, GRP78 and the proportion of DNA synthesis phase were all higher than those in high glucose siSR-A group and normal glucose siNC group (all P<0.05). Conclusion: High glucose can promote abnormal cell proliferation, increase mesangial matrix production and enhance oxidative stress response through upregulating SR-A expression, and ultimately aggravate cellular inflammatory damage in HMC, which may be associated with NLRP3-Caspase-1-IL-1β pathway regulated by SR-A expression